Green approach for synthesis of gold nanoparticles from Nigella arvensis leaf extract and evaluation of their antibacterial, antioxidant, cytotoxicity and catalytic activities. (3rd April 2018) - Chahardoli, Azam; Karimi, Naser; Sadeghi, Fatemeh; Fattahi, Ali
Abstract: In the present work, we studied the reduction of gold ions into gold nanoparticles using Nigella arvensis leaf extract in the one-step green synthesis method. The formation of N. arvensis gold nanoparticles (NA-GNPs) was confirmed by UV–Vis spectroscopy, XRD, FT-IR and TEM analyses. The XRD pattern confirmed the crystal structure of NA-GNPs, and TEM image showed the small size (3–37 nm) and almost spherical shape of NA-GNPs. NA-GNPs have not shown enhanced antioxidant properties compared to the plant extract while they were active against the clinical isolated bacterial strains. These nanoparticles showed the cytotoxicity effects against H1299 and MCF-7 cancer cell lines with an IC50 value of 10 and 25 μg/ml, respectively. The extract of N. arvensis contained 212 μg/ml flavonoids and 145 μg/ml phenolic compounds. The contents of total phenolics and flavonoids of biosynthesized NA-GNPs were 68 and 189 μg/ml, respectively. Plant extract and NA-GNPs exhibited a maximum DPPH scavenging activity of 32% and 12%, respectively. The catalytic activity of NA-GNPs against methylene blue was 44%. In conclusion, these results suggest that NA-GNPs can act as a promising candidate for different medical applications produced by cost-effective, eco-friendly and straightforward green method.